SP-1-activated LINC01016 overexpression promotes gastric cancer invasion and metastasis through inhibiting EIF4A3-mediated MMP9 mRNA decay - Ying Sun; Hui Zhang; Duan-bo Shi; Peng Gao (Cell Death and Disease)
Abstract Long noncoding RNAs (lncRNAs) are key regulators during gastric cancer (GC) development and may be viable treatment targets. In the present study, we showed that the expression of the long intergenic noncoding RNA 01016 (LINC01016) is significantly higher in GC tissues with lymph node metastasis (LNM) than those without LNM. LINC01016 overexpression predicts a poorer relapse-free survival (RFS) and overall survival (OS). Furthermore, we found that LINC01016 is activated by transcriptional factor SP-1 and contributes to the overt promotion of cell migratory ability. EIF4A3 was identified as a binding partner of LINC01016 by RNA pull-down assay, mass spectrometry and western blot. We determined that LINC01016 can blocks the binding of EIF4A3 to MMP9 mRNA, thereby inhibiting EIF4A3-mediated nonsense-mediated RNA decay (NMD), increasing MMP9 mRNA level and protein expression levels to promote tumor progression. LINC01016 or LINC01016-mediated EIF4A3/MMP9 may be potential therapeutic targets for patients with GC.